Effects of Lactiplantibacillus plantarum HNU082 intervention on fungi and bacteriophages in different intestinal segments of mice - Xinlei Liu; Zhe Han; Wenyao Ma; Weipeng Cui; Dongyu Zhen; Shuaiming Jiang; Jiachao Zhang (BMC Microbiology)
Abstract Background Gut fungi and bacteriophages, as members of the gut microbiota, can affect the interactions between gut bacteria and the host, participate in host metabolism, and are associated with various diseases. Probiotics substantially influence gut fungi and bacteriophages, modulating their composition through both direct and indirect mechanisms, thereby influencing host health. Current research primarily focuses on the effects of probiotics on the intestinal bacterial community. However, the alterations in the compositions of gut fungi and bacteriophages following probiotic intervention are not yet fully understood. Therefore, this study used Lactiplantibacillus plantarum HNU082 (Lp082) as the research subject and aimed to investigate the changes of the gut fungi and bacteriophages in the small intestine and the large intestine after the gavage of Lp082. Results After probiotics entered the gut, the changes of the gut fungi and bacteriophages caused by the probiotics were more pronounced in the small intestine compared to the large intestine. The relative abundance of pathogenic fungi, such as Candida albicans, decreased in the small intestine. Furthermore, a strong positive correlation between the relative abundance of bacteriophages and their host bacteria in the gut was observed. The relative abundance of both Clostridia class bacteria and their bacteriophages increased. Conclusions In summary, the effects of probiotics on gut fungi and bacteriophages differed between the small intestine and the large intestine. This study contributed to a better understanding of the impact of probiotics on gut fungi and bacteriophages and provided data support for the association and dynamic changes between gut bacteria and their bacteriophages.